PENGEMBANGAN SAHLA ARABIC FLIP BOOK (SABILI) SEBAGAI MEDIA PEMBELAJARAN KETERAMPILAN MEMBACA BAHASA ARAB KELAS X SMA KABUPATEN TEGAL: DEVELOPMENT OF SAHLA ARABIC FLIP BOOK (SABILI) AS A LEARNING MEDIA FOR ARABIC READING SKILLS FOR GRADE X STUDENTS OF SENIOR HIGH SCHOOL IN TEGAL DISTRICT - Muchlisin Nawawi; Aisyah Amar Aulia; Darul Qutni (Universitas Negeri Semarang, 2024)
This research is motivated by the lack of enthusiasm among students in participating in Arabic reading lessons at Islamic High Schools in Tegal Regency, due to teachers not maximizing the use of teaching media in addition to teaching modules, despite the availability of various facilities at the school. With the technological advancements happening today, the presence of digital learning media greatly aids both teachers and students in conducting learning inside and outside the classroom. Therefore, the researcher developed the digital educational media SABILI (Sahla Arabic Flip Book) to support the learning of Arabic reading skills for tenth-grade high school students. The objectives of this research are to (1) identify the needs of teachers and students for the development of the digital educational media SABILI (Sahla Arabic Flip Book) for Arabic reading skills, (2) develop a prototype of the digital educational media SABILI (Sahla Arabic Flip Book) for Arabic reading skills, and (3) determine the validation of teachers and experts regarding the digital educational media SABILI (Sahla Arabic Flip Book) for Arabic reading skills. This research is a research and development (R&D) study. Data collection in this study was carried out through non-test techniques. The non-test data instruments used included instruments for teacher and student needs which were distributed before the SABILI (Sahla Arabic Flip Book) prototype was developed, and expert validation instruments to assess the prototype after it was developed. In addition, interview and documentation techniques were also used to enhance the researcher's knowledge regarding the needs of teachers and students for the SABILI (Sahla Arabic Flip Book) educational media. The results of the study indicate that teachers and students desire the development of the SABILI (Sahla Arabic Flip Book) educational media for Arabic reading skills. The average score of the overall book feasibility standards is 89.37 in the range of 86-100, which falls into category 4 (very feasible), thus it can be concluded that the SABILI (Sahla Arabic Flip Book) educational media is very feasible to be used as a learning medium to support Arabic reading skills.